Mechanisms of formation of Al4Cu9 during mechanical alloying: An experimental study. (1st April 2015) - Besson, R.; Avettand-Fènoël, M.-N.; Thuinet, L.; Kwon, J.; Addad, A.; Roussel, P.; Legris, A.
Abstract: In spite of its complex structure, the Cu-rich γ1 -Al4 Cu9 compound is frequently observed in Al–Cu processing. In order to better understand the intriguing formation of this compound, a thorough experimental study of Al–25 at.% Cu mixtures produced by mechanical alloying (MA) was performed. Strong morphological changes are found to occur for moderate milling times. γ1 -Al4 Cu9 is formed during the early milling steps (5.5 h), its volume fraction increasing continuously with milling time, while the equilibrium θ-Al2 Cu expected for this composition is detected only for longer times (90 h). Whereas the early formation of γ1 suggests that its nucleation should occur at Al/Cu interfaces, direct visualization reveals the presence of γ1 crystallites within Cu-rich zones. The thermal instability of MA-formed γ1 -Al4 Cu9 is evidenced, this phase evolving towards θ-Al2 Cu at temperatures lower than those predicted for equilibrium conditions. These observations indicate that γ1 -Al4 Cu9 may be able to form through non-thermally activated mechanisms.